Determinants of Net Interest Margin in Indonesian Conventional Banks: Evidence from 2020–2024: (Quantitative Study on Conventional Banks Listed on the Indonesia Stock Exchange for the Period 2020–2024) - Cindy Zannah; Nurhana Dhea Parlina (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), and Operating Expenses to Operating Income (BOPO) on Net Interest Margin (NIM) in conventional banks listed on the Indonesia Stock Exchange during the 2020-2024 period. This study uses a quantitative approach with an associative research design. The sample was selected using purposive sampling and consisted of 11 conventional banks, resulting in 55 firm-year observations. The data were obtained from annual financial reports, official publications, and relevant banking sources. The data were analyzed using multiple linear regression with IBM SPSS Statistics 25, while the Cochrane-Orcutt method was applied to correct positive autocorrelation in the final model. The results show that CAR has a positive and significant effect on NIM, while NPL and BOPO have negative but insignificant effects on NIM. Simultaneously, CAR, NPL, and BOPO have a significant effect on NIM. The adjusted R-square value of 0.099 indicates that the independent variables explain 9.9% of the variation in NIM. These findings imply that capital adequacy remains an important internal factor in maintaining net interest margins, while credit risk control and operational efficiency should continue to be improved.